Experiencing a wedding website using augmented reality / Aini Nadia Pungut - Pungut, Aini Nadia (2017)
Wedding website is a must for bride and groom to be to look for their wedding dress, wedding services and wedding consultation. The problem for this project are the boutique located at different district and far from each branch of boutique. It cost more to the customer and also the owner of the boutique as to attend the customer because the customers need to go to both boutique to see which kind of wedding dress that suitable for them. By having the wedding website, they can look for the wedding dress first before going to the boutique. The methodology that used for this project is Waterfall methodology and uses up 4 phases only. Augmented reality tools has been used in this project to enhance the static wedding website. One of the augmented tools that has been used in this project is Aurasma. Augmented Reality tools is known as Aurasma, one of the tools that provide the functionality for experiencing the reality using smartphone or using computer desktop. For this project, Aurasma using smartphone has been used to experiencing real-world environment. From the testing that has been done are people more exciting using Aurasma and more flexible for them to view full image of wedding dress. The expected result from this project is people tend to get experience real-world environment using Augmented Reality tools in the wedding website. The future work that can be recommend for this project are Aurasma should be apply to all items in the website, add features for calculating budget and add features for booking the wedding dress.